Peran Media Massa dalam Pencegahan Potensi Bencana Alam: Kajian Berita Konflik Tambang Pasir Besi - Perdana, Dionni Ditya (LPPM Stikosa - AWS, 2024)
Conflicts of interest are inevitable when the natural potential is harnessed in mining. This happened in Seluma Regency, Bengkulu Province, Indonesia, in a conflict due to the impact of iron sand mining involving the community, mine owners, and the government. Mining always intersects with environmental degradation, which leads to disaster triggers. This is also inseparable from the media attention shown in its reporting. The purpose of this study is to determine the role of the media in preventing potential disaster events, specifically related to reporting on mining conflicts in the iron sand mines in the Seluma district. This research uses a descriptive qualitative approach. The analysis method was carried out using a framing analysis from Robert N. Entman, where researchers will dismantle the construction of news submitted by the media from the iron sand mine conflict in Seluma Regency. The study's findings suggest that the information conveyed in the news of iron sand mining conflict emphasizes the impact on the survival of the fishermen of the surrounding community. This research shows that the media can play a role in preventing potential natural disasters through reporting on mining conflicts with the perspective of sustainability and environmental sustainability.